Plasticity, Flow Liquefaction, and Cyclic Mobility in Liquefiable Soils with Low to Moderate Plasticity - Carmine P. Polito; James R. Martin (CivilEng)
Over the past several decades, extensive research has advanced the understanding of liquefaction in clean sands and sand–silt mixtures under seismic loading. However, the influence of plastic (i.e., clayey) fines on the liquefaction behavior of sandy soils remains less well understood. This study investigates how the quantity and plasticity of fines affect both the susceptibility to liquefaction and the resulting failure mode. A series of stress-controlled cyclic triaxial tests were conducted on sand specimens containing varying proportions of non-plastic silt, kaolinite, and bentonite. Specimens were prepared at a constant relative density with fines content ranging from 0% to 37%. Two liquefaction modes were examined: flow liquefaction, characterized by sudden and large strains under undrained conditions, and cyclic mobility, which involves gradual strain accumulation without complete strength loss. The results revealed a clear relationship between soil plasticity and liquefaction mode. Specimens containing non-plastic fines or fines with a liquid limit (LL) below 20% and a plasticity index (PI) of 0 exhibited flow liquefaction. In contrast, specimens with LL > 20% and PI ≥ 7% consistently displayed cyclic mobility behavior. These findings help reconcile the apparent contradiction between laboratory studies, which often show increased liquefaction susceptibility with plastic fines, and field observations, where clayey soils frequently appear non-liquefiable. The study emphasizes the critical role of plasticity in determining liquefaction type, providing essential insight for seismic risk assessments and design practices involving fine-containing sandy soils.